Community Participation and its Impact on Sustainable Educational Infrastructure Development in Rural Areas of Niger State - Lakan, M. J. (Journal of Research in Adult and Continuing Education, 2025)
This study investigated the role of community participation in fostering sustainable development of educational infrastructure in rural areas of Niger State. Using quantitative method, data were collected from community leaders, school heads, parents, and government officials across selected rural communities in Niger State. The sample size was determined using the Taro Yamane formula, resulting in 349 respondents. A multistage sampling technique was employed. Data were collected through a structured questionnaire designed on a 5-point Likert scale. For data analysis, descriptive statistics such as frequency counts, percentages, means, and standard deviations was used to answer the research question. The findings revealed that community involvement in planning, construction, and maintenance of school infrastructure significantly influenced the sustainability of such projects. In communities where resources—such as labor, land, and local materials were contributed, projects exhibited higher levels of maintenance and utilization. Based on these findings, the study recommended that government and educational authorities should institutionalize participatory frameworks that involve communities from the planning to execution stages of school projects. Adequate funding, training, and policy support should be provided to communities. This includes grants or matching funds for community-led school projects and strengthening School-Based Management Committees [SBMCs] through training and recognition. Targeted sensitization campaigns should be launched to raise awareness about the importance of community involvement in school infrastructure.
Keywords: Community Participation; Sustainable Development; Educational Infrastructure; Rural Education; Stakeholder Engagement; School Facilities; Grassroots Involvement